PTH-016 Recurrence after advanced colorectal endoscopic resection results in a substantial cost burden. Issue 2 (June 2019) - Emmanuel, Andrew; Williams, Sophie; Gulati, Shraddha; Lapa, Christo; Gunasingam, Nishmi; Burt, Margaret; Hayee, Bu; Haji, Amyn
Abstract : Introduction: Little is known about the cost of treating recurrence after colorectal endoscopic resection (ER). Endoscopic mucosal resection (EMR) has proven efficacy and safety and is the procedure of choice for the majority of western endoscopists. However, recurrence is not infrequent but no studies examine the cost associate with ER taking into account treatment for recurrence. We evaluated the total cost of ER at a tertiary centre. Methods: ER (EMR, ESD and Hybrid ESD) of large (≥20 mm) colorectal tumours with at least the first surveillance colonoscopy were included. Surveillance was performed at 3–6 months and 12 months. Procedure costs were based on NHS national tariffs. Total costs included the cost of all endoscopic or surgical treatments and surveillance to 12 months. Cost of treatment for patients with recurrent adenomas and those without were compared. Results: Of 626 ER of large colorectal tumours, 473 (98% of eligible patients) had undergone at least the first surveillance colonoscopy. Overall, recurrence occurred in 69 (14.7%). Patients with recurrence required a median of 2 ERs (range 2–6). 8 patients required surgery for recurrence. Mean cost of treating those with recurrence was £3976 versus £1539 for those without (p<0.001). 51% of lesions had been subjected to prior failed attempts at resection or extensive (≥6) biopsy sampling and these were significantly more likely to recur (OR 3.8, 95% CI 2.1–6.9, p<0.001). The cost of treating these patients was significantly more than those with minimal or no manipulation (p=0.001). Recurrence was less likely after ESD (OR 0.25, 95% CI 0.08–0.82, p=0.01). Conclusion: There is a substantial cost associated with the treatment of recurrence after ER which has not been considered in studies evaluating the efficacy of EMR. Injudicious prior manipulation contributes to the heavy cost burden. ESD should be evaluated more closely as it results in fewer subsequent treatments for recurrence and the possibility of longer surveillance intervals.